Asymmetric volatility spillovers between developed and developing European countries - Mattia Bevilacqua (Magyar Nemzeti Bank, 2018)
This paper aims to examine the volatility spillovers among three asset classes, namely, equity, currency and credit among developed European countries and developing Central Eastern European countries in response to political, economic and financial events occurred in the Eurozone in the last decade. We use a different version of the Diebold-Yilmaz spillovers index in order to take into account the volatility asymmetry effect under both its leverage effect and, also, in relation to separated good or bad news. The first may be due to positive or negative shocks of identical size, whereas the latter may be due to good or bad news impacting separately. We find that the stock market is the main channel through which volatility spills over among these countries with a clear role as volatility transmitters for the developed EU stock markets. The volatility leverage effect is evident mainly for the equity market, while it emerges only after the Eurozone sovereign debt crisis for the credit market. The Brexit vote is found to be the main event contributing to volatility spillovers in the currency market with the British pound transmitting positive volatility to the system. The Italian CDS market is found to play a crucial role during the Eurozone sovereign debt crisis, while the German CDS market is found to be more stable and mainly transmitting positive volatility. The European Central Banks policies, such as, LTRO and QE result into a reduction of negative volatility spillovers and into an increase of positive volatility spillovers in the credit market. According to the considered asset classes and time period, we detect positive and negative volatility spillovers among the selected countries in Europe showing how different events might contribute to different, beneficial or harmful, reactions within the system.
Keywords: C58; D53; F3; G15; 330; Volatility Spillovers; Asymmetric Volatility; Stock Markets; Currency Market; Credit Markets